Christology and the Synoptic Problem - Head, Peter M. (1995)
A dissertation examining and evaluating the christological argument for Markan priority in view of recent scholarship on the synoptic problem which advocates Markan posteriority.
Keywords: Christology; Synoptic Problem; gospels. synoptic gospels; New Testament